2022
DOI: 10.1111/hae.14518
|View full text |Cite
|
Sign up to set email alerts
|

Towards novel treatment options in von Willebrand disease

Abstract: Deficiency or dysfunction of von Willebrand factor (VWF) is associated with a bleeding disorder known as von Willebrand disease (VWD). The clinical manifestations of VWD are heterogeneous, and are in part dictated by the structural or functional defects of VWF. The tools to control bleeding in VWD are dominated by VWF concentrates, desmopressin and antifibrinolytic therapy. In view of these treatments being considered as effective, it is surprising that quality‐of‐life studies consistently demonstrate a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Nevertheless, the apparent neglect of this patient population has been recognized, and several new therapies are now under development. 46,66 Coincident with these advances to clinical care, further investigation continues into VWF biology, and in particular into a range of nonhemostatic functions that could be adversely affected in VWD. [67][68][69]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the apparent neglect of this patient population has been recognized, and several new therapies are now under development. 46,66 Coincident with these advances to clinical care, further investigation continues into VWF biology, and in particular into a range of nonhemostatic functions that could be adversely affected in VWD. [67][68][69]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the pathophysiology of bleeding in VWD is complex and involves deficiency of the multimeric glycoprotein, VWF, as well as FVIII, in addition to multi-ple specific functional VWF defects (i.e., impaired platelet, collagen or FVIII binding). 45,46 This results in challenges designing and implementing treatments, as well as performing clinical trials to evaluate novel VWD therapies.…”
Section: New Treatment Options For Vwd: An Update 41 Introductionmentioning
confidence: 99%
“…While it is already approved for hemophilia A patients by European Medicines Agency (EMA) and U.S. Food and Drug Administration (FDA), 55 there is still a need for more research in VWD patients. [56][57][58][59] Seminars in Thrombosis & Hemostasis © 2024. Thieme.…”
Section: Emicizumabmentioning
confidence: 99%
“…False negatives were deemed more concerning because specific treatment approaches are needed for type 2 VWD (such as VWF concentrates rather than desmopressin) 5,7 . Desmopressin raises VWF levels by release of endothelial stores and can be effective in many type 1 VWD patients 25 . The treatment is less effective or even contraindicated in type 2 VWD because a functionally abnormal protein is released 9 .…”
Section: Von Willebrand Factor Testing Ratiosmentioning
confidence: 99%
“…5,7 Desmopressin raises VWF levels by release of endothelial stores and can be effective in many type 1 VWD patients. 25 The treatment is less effective or even contraindicated in type 2 VWD because a functionally abnormal protein is released. 9 A recently published meta-analysis also showed that using an activity/antigen ratio <0.7 versus a lower cutoff was more accurate for diagnosis of type 2 disease with a sensitivity of 0.90 and specificity of 0.91.…”
Section: Von Willebrand Disease Testing Backgroundmentioning
confidence: 99%